Pengaruh Pendidikan Kesehatan dengan Media Video Terhadap Pengetahuan dan Sikap Remaja Tentang Pencegahan Kehamilan Usia Anak Di SMA 1 Bayan - Faizaturrahmi, Eka; Aprianti, Nurannisa Fitria (Jurnal Kesehatan Qamarul Huda, 2024)
Adolescent girls who marry or become pregnant before the age of 20 are at risk of maternal and child deaths, birth defects, pregnancy complications, low birth weight, sexually transmitted infections, and postpartum depression. The aim of this research is to determine the effect of video media on teenagers' knowledge and attitudes about preventing child pregnancy at SMA 1 Bayan. The type of research used is experimental research using pre-experimental techniques. This research used a one group pretest posttest design approach, a sample of 65 people using probability sampling technique. Data collection uses a questionnaire. Data processing uses univariate and bivariate analysis. The results of this research were that the knowledge of respondents before being given health education using video media was mostly poor knowledge as many as 34 respondents (52.3%) and after being given health education using video media most of the knowledge was good as many as 37 respondents (57.0%) and the attitudes of respondents before it was given after being given health education using video media mostly had a negative attitude as many as 38 respondents (58.5%) and after being given health education using video media the majority had a positive attitude as many as 53 respondents (81.5%). The Paired Samples Test results obtained a knowledge p-value of 0.003 and an attitude p-value of 0.001. The conclusion of the research results shows that there is an influence of health education using video media on teenagers' attitudes about preventing childhood pregnancies. Advice is expected from educational institutions, especially midwifery, that it can be used as a reference material and as literature in midwifery education as well as a reference in providing education to teenagers about preventing child pregnancy.